Impact of par-baking and storage conditions on the quality of par-baked and fully baked bread. (May 2017) - Debonne, Els; Van Bockstaele, Filip; Philips, Euge; De Leyn, Ingrid; Eeckhout, Mia
Abstract: Par-baking (PB) contributes to the extension of the microbiological and technological shelf-life of food products. The impact of processing conditions on the quality of PB bread, either when PB or fully baked (FB), was investigated. Processing conditions included PB time (8 and 13 min), temperature (150, 175 and 200 °C), amount of steam (200 and 600 mL) and storage temperature (ambient and frozen temperature) before fully baking. Volume, weight, crust color, crust thickness and crumb/crust texture of PB and FB breads were evaluated. PB temperature showed the most significant overall effect on bread quality. Influence of PB time was expressed in the weight of the FB bread, not in the weight of the PB bread. The storage temperature of the PB breads had the most significant influence on the texture characteristics of the FB breads. Surprisingly, PB and FB bread volume was not affected by PB time, steam and storage temperature. Highlights: Par-baking temperature has the biggest overall effect on par-baked and rebaked bread. Combination of baking temperature and time has an important influence on L* of the crust. Volume of par-baked bread is affected by par-baking temperature and proving. Frozen storage of par-baked bread influences bread color and texture.